The Analysis of Wages and Productivity in Iran’s Industry (1994- 2000) - Abdollah Taheri (فصلنامه پژوهش‌های اقتصادی ایران, 2004)
The existence of relationship between wages and labour productivity has been studied at the microeconomic level, in the process industrial development, and different wage systems based on labour productivity has emerged in the process of industrial growth. In these systems, called “payment by results”, aggregate or partial wages are related to individual or group efficiency. In almost all collective labour agreements “payment by results” is the main issue to be negotiated. The relationship between wages and productivity at the macroeconomic level is usually examined from economic stabilization and inflation control standpoint, as well as on the basis of the benefit gained by the labour force from productivity achievements. This paper measures labour productivity for the period of 1994- 2000 in industrial activities for the first time in Iran by estimation of “Generalized Average Labour Productivity”, and analyses its relationship with wages, and also discusses its theoretical implications. The findings of the research show that for the period examined, there was a direct relationship between wages and productivity in industrial avtivities and the structure of such relationship in various industrial activites was essentially the same.